Numerical method for an assessment of steady and motion-excited flowfields in a transonic cascade wind tunnel. (25th August 2017) - Tateishi, Atsushi; Watanabe, Toshinori; Himeno, Takehiro; Uzawa, Seiji
Abstract: This article presents a numerical method and its application for an assessment of the flow field inside a wind tunnel. A structured computational fluid dynamics (CFDs) solver with overset mesh technique is developed in order to simulate geometrically complex configurations. Applying the developed solver, a whole transonic cascade wind tunnel is modeled and simulated by a two-dimensional manner. The upstream and downstream periodicity of the cascade and the effect of the tunnel wall on the unsteady flow field are focused on. From the steady flow simulations, the existence of an optimum throttle position for the best periodicity for each tailboard angle is shown, which provides appropriate aerodynamic characteristics of ideal cascades in the wind tunnel environment. Unsteady simulations with blade oscillation is also conducted, and the difference in the influence coefficients between ideal and wind tunnel configurations becomes large when the pressure amplitude increases on the lower blades.